Safety and Efficacy of Mechanical Thrombectomy Using Tigertriever as a Rescue Device After Failed Aspiration—Single Center Experience - Piasecki, Piotr; Wierzbicki, Marek; Narloch, Jerzy (Frontiers in Neurology, 2021)
INTRODUCTION We evaluated the safety and efficacy of new stent retriever – Tigertriever - after failed aspiration. MATERIALS AND METHODS Patients with acute ischemic stroke treated with Tigertriever between January 2018 and March 2020 were included in the study. Treatment results of Tigertriever in rescue therapy (after failed aspiration) were evaluated. Periprocedural data were retrospectively analyzed. RESULTS 30 patients were treated with Tigertriever (14M/16F). There were 20 rescue thrombectomies after failed aspiration. Tigertriver successful recanalization rate (mTICI  2B) was 70%: 65% in rescue therapy and 80% in first-line therapy. The type of first line treatment had no impact on mRS after 1 month and 3 months (ns). There was significant improvement in NIHSS in all patients (mean NIHSS: 17 vs 10, p=0.028), in rescue treatment (mean NIHSS: 17 vs 11, p=0.048) and in first line treatment (mean NIHSS: 16 vs 8, p=0.0005). Better results in NIHSS at discharge were linked with: first pass success (p=0.002), better mTICI at the end of the procedure (p=0.0006), administration of rtPA (p=0.013). CONSLUSIONS There was no difference in safety profile, short- and long-time results between Tigertriever thrombectomy done as a rescue or first line therapy. Tigertriever first pass success led to better mRS score at 3 months. Tigertriver is useful tool in first-line and rescue treatment.